EXPLORING EFL LEARNERS’ WRITING SELF-EFFICACY - Pabangke, Alfin; Sallata, Yizrel Nani; Patanduk, Sushy Teko (Teaching English as a Foreign Language Overseas Journal, 2024)
This study explores the factors contributing to the writing self-efficacy of EFL (English as a Foreign Language) learners at Universitas Kristen Indonesia Toraja (UKI Toraja). Using a qualitative approach with a case study design, the research involved five seventh-semester students from the English Education Study Program. Data were collected through in-depth interviews and analyzed using Miles and Huberman's qualitative analysis techniques. The findings reveal that students' writing self-efficacy is influenced by both internal and external factors. Internal factors include diverse writing experiences, motivation and initiative, and emotional states such as anxiety or enthusiasm during writing. External factors encompass inspiration from peers' and lecturers' writing, social support, and collaborative learning environments. Challenges such as lack of motivation, difficulty in generating ideas, and language barriers also play a significant role.